Problematic Issues of Preventive Activities of Investigators and Interrogators in the Legislation of Ukraine and Some Foreign Countries - R. M. Balats (Bulletin of Kharkiv National University of Internal Affairs)
The author has carried out a comparative analysis of the normative provisions of the legislation of Ukraine and some foreign countries on preventive activities, in particular the regulation of tasks to identify the causes and conditions that contributed to the crime during the pre-trial investigation. The annual increase in the number of criminal offenses indicates the need to introduce the institution of preventive activities of investigators and interrogators into the current Criminal Procedural Code of Ukraine. The scientific views of scholars have been studied and the own vision of the raised problems has been developed.